Hydroxyapatite modified biochar material, preparation method thereof and application of hydroxyapatite modified biochar material in treatment of fluorine-containing wastewater

The Al-HAP/BC composite material prepared and modified by in-situ precipitation method solves the problems of high adsorbent cost and poor fluorine removal effect in fluorine-containing wastewater treatment in the prior art, achieves efficient and economical fluorine removal effect, and has good regeneration performance.

CN119771337APending Publication Date: 2025-04-08NANJING NORMAL UNIVERSITY

Patent Information

Application Number
CN202411877321.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, when treating fluorine-containing wastewater, the adsorbent has high cost, poor fluorine removal effect, and it is difficult to achieve efficient regeneration.

Method used

The hydroxyapatite-biochar composite material was prepared by in-situ precipitation method, and modified with metal aluminum ions to form an Al-HAP/BC composite material, which was applied to the treatment of fluorine-containing wastewater.

Benefits of technology

It has achieved low cost, high adsorption capacity and good regeneration performance, significantly improved the fluorine removal effect, and increased the adsorption efficiency by more than 5 times, and can still achieve a 60% fluorine removal efficiency after 5 reuses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771337A_ABST
    Figure CN119771337A_ABST
Patent Text Reader

Abstract

The invention relates to the field of wastewater treatment, and discloses a hydroxyapatite modified biochar material as well as a preparation method and application thereof in treatment of fluorine-containing wastewater. The preparation method comprises the following steps: preparing a hydroxyapatite-biochar composite material by using an in-situ precipitation method, and modifying by using metal aluminum ions, specifically, uniformly mixing peanut shell powder and anhydrous calcium chloride, dispersing, dropwise adding diammonium hydrogen phosphate for reacting, adjusting pH by using NaOH, stirring at constant temperature for reacting, washing with water and absolute ethyl alcohol to be neutral, and drying to obtain an HAP / C composite material; the HAP / C composite material is placed in a tubular furnace for pyrolysis, and an HAP / BC composite material is obtained; and adding an A1Cl3. 6H2O solution into the HAP / BC composite material, uniformly stirring, standing, carrying out suction filtration and washing until the HAP / BC composite material is neutral, and finally drying the HAP / BC composite material in a constant-temperature drying box to obtain the Al-HAP / BC composite material with low cost, large adsorption capacity and strong stable regeneration performance, and the obtained Al-HAP / BC composite material is applied to fluorine ion-containing wastewater, has a remarkable fluorine removal effect and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wastewater treatment, and in particular to a hydroxyapatite-modified biochar material and a preparation method thereof, and application of the biochar material in treating fluorine-containing wastewater. Background Art

[0003] Biochar (BC) is widely available, green and environmentally friendly, and has high economic benefits, but its single adsorption capacity is poor. Hydroxyapatite (HAP) is a common adsorption filter material with high porosity and specific surface area, and excellent fluoride adsorption potential. HAP is modified with metal cations, natural minerals, organic matter and carbon nanoparticles to achieve the purpose of deep fluoride removal, but at the same time, the high cost factor must also be considered, and the adsorption capacity needs to be further improved.

[0004] At present, the commonly used defluorination methods for fluoride wastewater at home and abroad mainly include adsorption, electrocoagulation, electrodialysis, ion exchange, precipitation, etc. Among these methods, the adsorption method has attracted widespread attention due to its low production cost, simple operating conditions and recyclability. There are many types of common defluorination adsorbents such as natural mineral materials, aluminum-based adsorbents, carbon-based adsorbents, etc., but the cost, defluorination effect and difficulty of some single adsorbents cannot achieve good results. It is necessary to prepare an adsorbent through modification or composite materials to improve the adsorption performance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a hydroxyapatite modified biochar material, a preparation method thereof and an application in treating fluorine-containing wastewater. A hydroxyapatite-biochar composite material is prepared by an in-situ precipitation method, and is modified by metal aluminum ions to obtain a modified hydroxyapatite-biochar material with low cost, large adsorption capacity and good stable regeneration performance. The material is applied to the treatment of fluorine-containing wastewater, has good fluorine removal effect, and has good application prospects.

[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0007] A method for preparing a hydroxyapatite-modified biochar material comprises the following steps:

[0008] Step 1, washing, drying, and crushing the peanut shells, and sieving them through a 100-mesh sieve to obtain peanut shell powder with uniform particle size;

[0009] Step 2, after the peanut shell powder and anhydrous calcium chloride are uniformly mixed, ultrasonic dispersion is performed, and then an equal volume of diammonium hydrogen phosphate is added dropwise at a rate of 1-2 mL / min using a peristaltic pump to react, the pH is adjusted to 9-12 with NaOH, the reaction is continued with constant temperature stirring, and the mixture is aged at 20-25° C. for 24 h, washed with water and anhydrous ethanol until neutral, and dried to obtain a HAP / C composite material;

[0010] Step 3, placing the HAP / C composite material in a tubular furnace for pyrolysis to obtain a HAP / BC composite material;

[0011] Step 4: Take the HAP / BC composite material and AlCl3·6H2O and add them to 50 mL of aqueous solution, stir evenly on a magnetic stirrer for 2 h, let it stand, filter with water using a microporous filter membrane until it is neutral, and finally place it in a constant temperature drying oven to dry, thereby obtaining the Al-HAP / BC composite material.

[0012] Furthermore, in step 1, step 2 and step 4, the drying temperature is 80° C. and the drying time is 12 hours.

[0013] Furthermore, in step 2, the mass ratio of peanut shell powder: anhydrous calcium chloride: diammonium hydrogen phosphate is 5-20:5:3.66.

[0014] Furthermore, in step 2, the ultrasonic dispersion time is 25-35 min; the reaction temperature is 20-60° C., and the reaction time is 2 h.

[0015] Furthermore, in step 3, the pyrolysis temperature is 450-750°C, the pyrolysis heating rate is 10°C / min, and the pyrolysis time is 2h.

[0016] Furthermore, in step 4, the mass ratio of the HAP / BC composite material to AlCl3·6H2O is 1:1-2.

[0017] Furthermore, in step 4, the stirring speed is 400 rpm, and the pore size of the microporous filter membrane is 0.45 μm.

[0018] The hydroxyapatite-modified biochar material prepared by the above preparation method has high adsorption capacity. Compared with the biochar material, the fluorine removal effect is improved by more than 5 times; it has excellent stability and reusability, and the fluorine removal efficiency can still reach more than 60% after repeating 5 times.

[0019] The hydroxyapatite-modified biochar material prepared by the above preparation method is used in treating fluoride-containing wastewater.

[0020] Furthermore, the fluorine concentration of the fluorine-containing wastewater is 5-80 mg / L.

[0021] Beneficial effects:

[0022] Compared with the prior art, the hydroxyapatite-modified biochar material and its preparation method and application in treating fluoride-containing wastewater of the present invention have the following advantages:

[0023] 1. The hydroxyapatite-modified biochar material prepared by the present invention uses biochar as the main raw material, has high economic benefits, and has physical and chemical properties such as porous structure, rich surface active groups, and contains a variety of mineral salts. It is often used as the preferred adsorption material, especially suitable for fluorine adsorption;

[0024] 2. By modifying the biochar-loaded hydroxyapatite, the material has a higher specific surface area, more pore structure and more active ion groups, and the adsorption capacity for fluoride ions is enhanced;

[0025] 3. The modification with hydrated aluminum chloride enhances the ion exchange capacity of hydroxyapatite. On the basis of the electrostatic attraction of biochar, it also strengthens the coordination exchange capacity of aluminum for fluorine, and increases the adsorption capacity for fluoride ions. Compared with single biochar material, the fluoride removal adsorption efficiency is increased by more than 5 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a visual appearance picture of the composite material prepared in Example 1;

[0027] Figure 2 These are SEM images of the composite materials prepared in Example 9 before and after modification, where a is BC, b is HAP, c is HAP / BC, and d is Al-HAP / BC;

[0028] Figure 3 is the X-ray spectrum of the composite material before and after adsorption in Example 9;

[0029] Figure 4 Is the FTIR infrared spectrum of the composite material before and after modification in Example 9.

[0030] Figure 5 is the different initial F in Example 9 - Variation curve of adsorption efficiency under concentration conditions;

[0031] Figure 6 This is a graph showing the repeated stability effect of the composite material prepared in Example 9. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described clearly and completely below, and the preferred embodiments in the description are only used as examples. All other embodiments obtained by those skilled in the art without making any creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a hydroxyapatite-modified biochar material comprises the following steps:

[0035] Step 1, washing the peanut shells, drying them in a drying oven at 80°C for 12 hours, crushing them, and sieving them through a 100-mesh sieve to obtain peanut shell powder with uniform particle size;

[0036] Step 2, 4 g peanut shell powder and 50 mL of 0.2 mol / L anhydrous calcium chloride were mixed evenly, ultrasonically dispersed for 30 min, 50 mL of 0.12 mol / L diammonium hydrogen phosphate was added dropwise at a rate of 1 mL / min using a peristaltic pump to react, the pH was adjusted to 10 with NaOH, constant temperature stirring was performed at 20° C., aged at 20-25° C. for 24 h, washed with water and anhydrous ethanol until neutral, and dried to obtain a HAP / C composite material;

[0037] Step 3, placing the HAP / C composite material in a tubular furnace for pyrolysis, wherein the pyrolysis temperature is 600° C., the pyrolysis heating rate is 10° C. / min, and after pyrolysis for 2 h, a HAP / BC composite material is obtained;

[0038] Step 4: Take 0.1 g of HAP / BC composite material and 0.2 g of AlCl3·6H2O and add them to 50 mL of aqueous solution, stir evenly at 400 r / min on a magnetic stirrer for 2 h, let it stand, filter with water using a 0.45 μm microporous filter membrane until it is neutral, and finally dry it in a constant temperature drying oven at 80°C to obtain an Al-HAP / BC composite material, such as Figure 1 The visual appearance is black powdery granules.

[0039] The Al-HAP / BC composite material prepared in Example 1 was applied to the adsorption of fluoride-containing wastewater. The specific steps are as follows: add the Al-HAP / BC composite material powder sample to 10 mg / L simulated fluoride-containing wastewater at a dosage of 1 g / L, stir magnetically for 12 hours, let stand for 2 hours, take the supernatant, and measure the fluoride ion concentration in the water using the ion selective electrode method (GB / 7484-87). The adsorption capacity of Example 1 was measured to be 9.492, and the fluoride removal rate was 94.92%.

[0040] The steps of Example 2-10 are basically the same as those of Example 1, except that the four factors of peanut shell powder mass, reaction temperature / °C, pyrolysis temperature / °C, and HAP / BC: aluminum chloride mass ratio are changed during the preparation process and applied to the adsorption of fluoride-containing wastewater. The factor conditions and defluorination adsorption efficiency are shown in Table 1 below.

[0041] Table 1 Parameter list of Examples 2-10

[0042]

[0043] The material prepared in Example 9 was selected for structural characterization, and the results are as follows:

[0044] 1. Morphological characterization of hydroxyapatite-modified biochar materials

[0045] The morphological changes of hydroxyapatite-modified biochar materials can be seen in Figure 2 , where a is BC, b is HAP, c is HAP / BC, and d is Al-HAP / BC. It can be seen from the figure that the surface of BC is smooth and has a porous structure, which provides a place for the loading of HAP. There are a lot of white agglomerates on the surface and in the pores of HAP / BC and Al-HAP / BC, and the surface area and particle porosity are increased, which improves the adsorption capacity of the material to a certain extent.

[0046] 2. Analysis of the content of hydroxyapatite-modified biochar material before and after adsorption (EDS)

[0047] X-ray spectrum analysis of a certain area of ​​hydroxyapatite modified biochar material shows Figure 3 As can be seen from the figure, the material is mainly composed of Ca, Al, O, and P elements, and the weight percentage (wt%) and atomic percentage (At%) of Ca and Al with P are compounded with the chemical characteristics of HAP, indicating that HAP is successfully loaded on BC. After adsorption, a new peak appears at 520eV, proving that it is the F element, indicating that the material has the ability to adsorb fluorine.

[0048] 3. FTIR infrared spectrum analysis of hydroxyapatite modified biochar material before and after modification

[0049] Infrared spectra of hydroxyapatite modified biochar materials before and after modification Figure 4 As can be seen from the figure, in the HAP / BC and Al-HAP / BC spectra, at a wavelength of 1095 cm -1 、1034cm -1 、601cm -1 and 568cm -1 There is a characteristic vibration peak of the phosphate group at a wavelength of 3430 cm -1 The infrared peaks around 1567-1627cm -1 The peak at the wavelength of 1024 cm is from the stretching vibration of the -OH group. -1 There is an Al-OH stretching bond at 400-800cm -1 The absorption peak at can be attributed to the stretching vibration of the metal oxygen bond, indicating that aluminum and HAP are successfully loaded on BC. By comparing the spectra of the three samples, it can be seen that the modification enhances the characteristic peak of the hydroxyl group and increases the area, which is F - The adsorption provides more active sites, which is beneficial to improving the efficiency of fluorine adsorption.

[0050] Embodiment 11

[0051] The material of Example 9 was used to adsorb fluoride-containing wastewater with different concentrations. The specific steps were as follows: Al-HAP / BC composite material powder sample was added to simulated fluoride-containing wastewater at a dosage of 1 g / L (5 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L), magnetically stirred for 12 h, and after standing for 2 h, the supernatant was taken and the fluoride ion concentration in the water was measured by ion selective electrode method (GB / 7484-87) to obtain different initial F - Adsorption capacity and adsorption efficiency under concentration conditions.

[0052] Adsorption effect and change curve Figure 5 As shown ( Figure 5 The horizontal axis represents different initial F - The left side of the ordinate represents the adsorption capacity in mg / g, and the right side represents the adsorption efficiency in %).

[0053] Depend on Figure 5 It can be seen that with the increase of initial concentration, the adsorption capacity of Al-HAP / BC composite material gradually increases, but the adsorption efficiency continues to decrease. The reason may be that at low concentrations, the adsorbent is not saturated and the fluoride ions that can be adsorbed are limited, so the adsorption capacity is low. With the increase of concentration, the content of fluoride ions adsorbed on the surface of the adsorbent gradually increases, and the surface adsorption sites gradually reach saturation, so the adsorption capacity increases, but the concentration of remaining fluoride ions in the solution increases, so the corresponding removal rate decreases.

[0054] Example 12

[0055] The material of Example 9 was used to conduct an adsorption regeneration experiment. The specific steps are as follows: the Al-HAP / BC material after the adsorption reaction was completed was washed and dried, a NaOH solution with a concentration of 0.1 mol / L was added and ultrasonically treated for 2 h, and then washed with deionized water and dried to obtain a primary regenerated adsorbent. The adsorbent was added to 10 mg / L simulated fluoride ion wastewater at a dosage of 1 g / L, magnetically stirred for 12 h, and allowed to stand for 2 h. The supernatant was taken and the fluoride ion concentration in the water was measured using the ion selective electrode method (GB / 7484-87). The cycle was repeated 5 times. The experimental results are as follows: Figure 6 As shown ( Figure 6 The horizontal axis in the middle represents the number of regenerations, the left side of the vertical axis represents the adsorption capacity in mg / g, and the right side represents the adsorption efficiency in %).

[0056] Depend on Figure 6It can be seen that after NaOH analysis, the adsorption capacity of Al-HAP / BC material for F- gradually decreased, and then the decline slowed down. After the fifth time, the adsorption and fluorine removal efficiency could still reach more than 60%, indicating that Al-HAP / BC has good recycling performance.

[0057] Comparative Example 1

[0058] A method for preparing a hydroxyapatite-modified biochar material comprises the following steps:

[0059] Except for excluding step 2 and step 4, the rest is the same as Example 1 to obtain BC material.

[0060] The BC material prepared in Comparative Example 1 was added to 50 mL of simulated fluoride-containing wastewater (10 mg / L) at a dosage of 1 g / L, and magnetically stirred for 12 h. After standing for 2 h, the supernatant was taken and the fluoride ion concentration in the water was measured using the ion selective electrode method (GB / 7484-87). The adsorption capacity of Comparative Example 1 was measured to be 1.845, and the fluoride removal rate was 18.45%.

[0061] Comparative Example 2

[0062] Except for excluding step 4, the rest is the same as Example 1 to obtain a HAP / BC composite material.

[0063] The HAP / BC composite material powder sample prepared in Comparative Example 2 was added to 50 mL of simulated fluoride-containing wastewater (10 mg / L) at a dosage of 1 g / L, and magnetically stirred for 12 h. After standing for 2 h, the supernatant was taken and the fluoride ion concentration in the water was measured using the ion selective electrode method (GB / 7484-87). The adsorption capacity of Comparative Example 2 was measured to be 5.562, and the fluoride removal rate was 55.62%.

[0064] In summary, the present invention provides a hydroxyapatite modified biochar material and its preparation method and application in treating fluorine-containing wastewater. A hydroxyapatite-biochar composite material is prepared by an in-situ precipitation method and modified by metal aluminum ions to obtain a modified hydroxyapatite-biochar material with low cost, large adsorption capacity and good stable regeneration performance. The material is applied to the treatment of fluorine-containing wastewater, has good fluoride removal effect, and has good application prospects.

[0065] The present invention and its embodiments are described schematically above, and the description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. Therefore, if a person skilled in the art is inspired by it and designs a structural method and an embodiment similar to the technical solution without creativity without departing from the purpose of the invention, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hydroxyapatite-modified biochar material, characterized in that: The following steps are involved: Step 1, washing, drying, and crushing the peanut shells, and sieving them through a 100-mesh sieve to obtain peanut shell powder with uniform particle size; Step 2, after the peanut shell powder and anhydrous calcium chloride are uniformly mixed, ultrasonic dispersion is performed, and then an equal volume of diammonium hydrogen phosphate is added dropwise at a rate of 1-2 mL / min using a peristaltic pump to react, the pH is adjusted to 9-12 with NaOH, the reaction is continued with constant temperature stirring, and the mixture is aged at 20-25° C. for 24 h, washed with water and anhydrous ethanol until neutral, and dried to obtain a HAP / C composite material; Step 3, placing the HAP / C composite material in a tubular furnace for pyrolysis to obtain a HAP / BC composite material; Step 4: Take the HAP / BC composite material and AlCl3·6H2O and add them to 50 mL of aqueous solution, stir evenly on a magnetic stirrer for 2 h, let it stand, filter with water using a microporous filter membrane until it is neutral, and finally place it in a constant temperature drying oven to dry, thereby obtaining the Al-HAP / BC composite material.

2. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: The drying temperature in step 1, step 2 and step 4 is 80° C. and the drying time is 12 h.

3. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: In step 2, the mass ratio of peanut shell powder: anhydrous calcium chloride: diammonium hydrogen phosphate is 5-20:5:3.

66.

4. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: The ultrasonic dispersion time in step 2 is 25-35 min; the reaction temperature is 20-60° C., and the reaction time is 2 h.

5. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: In step 3, the pyrolysis temperature is 450-750°C, the pyrolysis heating rate is 10°C / min, and the pyrolysis time is 2h.

6. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: In step 4, the mass ratio of the HAP / BC composite material to AlCl3·6H2O is 1:1-2.

7. The method for preparing a hydroxyapatite-modified biochar material according to claim 1, characterized in that: The stirring speed in step 4 is 400 rpm, and the pore size of the microporous filter membrane is 0.45 µm.

8. A hydroxyapatite-modified biochar material prepared by any one of the preparation methods of claims 1 to 7, characterized in that: The hydroxyapatite-modified biochar material has high adsorption capacity, and compared with the biochar material, the fluorine removal effect is improved by more than 5 times; it has excellent stability and reusability, and the fluorine removal efficiency can still reach more than 60% after being repeated 5 times.

9. Application of the hydroxyapatite-modified biochar material prepared by any one of the preparation methods of claims 1 to 7 in treating fluoride-containing wastewater.

10. The use according to claim 9, characterized in that: The fluorine concentration of the fluorine-containing wastewater is 5-80 mg / L.

Citation Information

Patent Citations

  • Preparation method of hydroxyapatite / bagasse active carbon

    CN103861567A

  • Preparation method of composite modified fluoride-removing adsorbent

    CN107096492A

  • Modified biomass charcoal adsorption material, preparation method and application thereof, and regeneration method of modified biomass charcoal adsorption material

    CN113117643A

  • Compound deep defluorination agent and preparation method thereof

    CN117964084A

Cited By

  • Method for preparing high-purity calcium fluoride through fluorine-containing wastewater resourceful treatment

    CN122426764A